Increasing the Effectiveness of the Implementation of the Green School Program in the Context of Instilling Environmentally Caring Character Values for Teachers at SD Negeri Candirejo Through the Mentoring Program for the 2022/2023 Academic Year - Paryati, Paryati (IJCER (International Journal of Chemistry Education Research), 2024)
This research aims to increase the effectiveness of implementing the Green School program in order to instill environmentally caring character values for teachers at SD Negeri Candirejo through a mentoring program for the 2022/2023 academic year. The research is expected to provide benefits to the school, teachers and students. Research is expected to be able to develop and expand the school's repertoire. Teachers can use the environment as a learning resource in accordance with the material being taught and students are expected to become more actively involved in the Green School program. This school action research is designed with a mentoring model using classroom action research procedures which are arranged according to the stages of planning, implementation, observation and reflection. The research was carried out in 2 cycles, namely cycles I and II with collaborative techniques from colleagues who assisted in observations. The research subjects were SD Negeri Candirejo teachers for the 20222/023 academic year, consisting of 10 teachers. Data collection techniques were carried out using observation and assessment methods. The research results were obtained based on observation and assessment using observation and assessment instruments.